Analysis of stewardess training of executive coach with reference to Semai Impian Sdn. Bhd. / Azlina Hassim - Hassim, Azlina (1995)
In this thesis, I will stress on the stewardess's training because of their importance as one of the backbone of the operation. By using them, the services can be provided efficiently in the cabin to the passengers. These will make the Executive Coach to be the priority among tlie various public transportation which can provide a high quality service.